Effectiveness of a quality management program in dental care practices - Götz, Katja; Campbell, Stephen M.; Broge, Björn; Brodowski, Marc; Wensing, Michel; Szecsenyi, Joachim (BMC oral health, 2014)
Structured quality management is an important aspect for improving patient dental care outcomes, but reliable evidence to validate effects is lacking. We aimed to examine the effectiveness of a quality management program in primary dental care settings in Germany.
Gesehen am 22.09.2020